Short Communication: A note on the new record of the amphibian fauna in Pulau Tinggi, Malaysia - Yin Hui Ng; Ngadi Ehwan; Badrul Munir Md-Zain; Md Zairi Zainal; MUHAMMAD ABU BAKAR ABDUL-LATIFF (Society for Indonesian Biodiversity, 2020)
Abstract. Ng YH, Ngadi E, Md-Zain BM, Md-Zairi Z, Abdul-Latiff MAB. 2020. A note on the new record of the amphibian fauna in Pulau Tinggi, Malaysia. Biodiversitas 21: 2425-2429. A survey of amphibian species in Pulau Tinggi was conducted from February to October 2019. The study was carried out using the Visual Encounter Survey method and the drift-fenced pitfall trap method. Based on previously published literature and the present survey, an updated checklist of amphibians is presented. In total, nine species were recorded that comprise three previously recorded species (Limnonectes blythii, Polypedates leucomystax and Odorrana hosii), and six new recorded species (Limnonectes deinodon, Polypedates dischantus, Microhyla heymonsi, Fejervarya limnocharis, Ingerophrynus parvus, and Kaloula pulchra).